COVID-19 Lesson for Respiratory Syncytial Virus (RSV): Hygiene Works - Andrea Gastaldi; Daniele Donà; Elisa Barbieri; Carlo Giaquinto; Louis J. Bont; Eugenio Baraldi (MDPI AG, 2021)
Respiratory syncytial virus (RSV) is a leading cause of acute lower respiratory tract infections (LRTIs) in infants worldwide. The global direct medical cost associated with RSV LRTIs reaches billions of dollars, with the highest burden in low-middle-income countries. Many efforts have been devoted to improving its prevention and management, including both non-pharmaceutical and pharmaceutical strategies, often with limited routine use in high-income countries due to high costs. During the ongoing COVID-19 pandemic, a dramatic decrease in RSV infections (up to 70-90%) has been reported around the globe, directly related to the implementation of containment measures (face masks, hand hygiene, and social distancing). Primary prevention has demonstrated the highest cost effectiveness ratio in reducing the burden of a respiratory infection such as RSV, never reached before. Thus, we emphasize the importance of non-pharmaceutical preventive hygiene measures that should be implemented and maintained even after the COVID-19 outbreak.